First evidence of coexistence of Pseudo Pelger Huet anomaly and balanced translocation in a two decades retrospectively exposed human subject - Rajesh Kumar Chaurasia; Ranjana S. Pathak; Anjana Goel; Kapil B. Shirsath; Nagesh N. Bhat; Arshad Khan; Balvinder K. Sapra (Scientific Reports)
Abstract This study investigated the long-term stability of cytogenetic and morphological markers, including dicentric chromosomes (DC), unbalanced translocation (UT), balanced translocation (BT), and Pseudo Pelger-Huët Anomaly (PPHA), in a radiation worker exposed to an acute dose of 60Co-γ radiation. Initial dose assessment, one week after exposure via Thermoluminescent dosimeters (TLDs) and DC, yielded a physical dose of 438.8 mGy and a biological dose of 398 mGy respectively. A follow-up biodosimetry evaluation, conducted 24 years postexposure, yielded a dose estimate of 449 mGy on the basis of BT, closely matching the initial TLD measurement (+ 2.3% relative error). In contrast, the DC, UT, and micronuclei (MN) frequencies fell within the background range, confirming their instability over time. We also assessed the presence of PPHA in blood smears from the same volunteer. PPHA, a morphological marker of neutrophils originating exclusively in vivo from bone marrow progenitor cells, demonstrated a more than twofold increase in frequency compared to background levels, suggesting an association with radiation exposure. This is the first report of concurrent BT and PPHA persistence in the same individual, demonstrating the suitability of these biomarkers for retrospective detection of past radiation exposure. BT offered reliable dose reconstruction decades after exposure. We could not translate the PPHA yield into an absorbed dose, as no in-house dose‒response curve was established.